Design of porous and fish scale-like nanofibers for the reinforcement of transparent composites. (15th December 2021) - Xuan, Hongyun; Wei, Shuo; Xiong, Feng; Zhang, Zhuojun; Xue, Ye; Sun, Miao; Li, Biyun; Yuan, Huihua
Graphical abstract: Highlights: Novel porous and fish scale-like PLLA nanofibers were prepared. This was achieved by combining electrospinning and subsequent acetone treatment. The mechanical properties of PMMA were improved and the transparency was constant. Good interfacial compatibility was shown between the reinforced fiber s and matrix. Abstract: The nanofiber-matrix interaction remains one of the primary factors that governs the performance of transparent composites. Here, a novel porous and fish scale-like poly(L)-lactide (PLLA) ultrafine fiber was prepared by combining electrospinning and subsequent acetone treatment. Following embedding of the electrospun PLLA fibers into a poly(methyl methacrylate) (PMMA)-acetone solution, the porous and fish scale-like PLLA fibers were found to interlock with the PMMA matrix. The mechanical properties of composites reinforced with these fibers were improved in comparison with those of a pure PMMA resin, while the transmittance of the composite was maintained above 80% at a wavelength of 589 nm. Observation of the cross-sectional morphology of the prepared material and subsequent molecular dynamics analysis showed that the fibers can significantly enhance the interfacial compatibility between the PLLA fibers and the PMMA matrix. This novel fiber can therefore be considered to be an effective candidate for the reinforcement of transparent composites.